2012
DOI: 10.1542/hpeds.2011-00112
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Treatment Variability of Refractory Kawasaki Disease: A Multicenter Analysis From 2005 to 2009

Abstract: Objective: Approximately 10% to 15% of Kawasaki disease (KD) is refractory to treatment with initial intravenous immunoglobulin (IVIG). However, there is no consensus on pharmacologic treatment of refractory KD (rKD). Demographic characteristics of patients with rKD and regional variability in their treatment in the United States have not been reported on a large scale. The goal of this study was to describe the demographic and treatment variability in rKD by using a large multi-institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…IVIG was the second-line drug of choice in 64.5% of the patients unresponsive to initial IVIG treatment in a previous investigation of 5,633 patients in the United States10). A nationwide survey in Japan showed that second-line treatment with additional IVIG was performed in 44.1% of hospitals and that it was combined with other drugs in 26% of hospitals11).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…IVIG was the second-line drug of choice in 64.5% of the patients unresponsive to initial IVIG treatment in a previous investigation of 5,633 patients in the United States10). A nationwide survey in Japan showed that second-line treatment with additional IVIG was performed in 44.1% of hospitals and that it was combined with other drugs in 26% of hospitals11).…”
Section: Discussionmentioning
confidence: 97%
“…Despite the significant level of unresponsiveness to first-line treatment in patients with KD, the best second-line treatment remains unknown. The administration of a second IVIG dose is currently the most common therapeutic strategy in unresponsive cases1011). Although the rate of unresponsiveness to second-line treatment with IVIG has been reported as 22%–49% 121314151617), no studies have reported on the prediction of unresponsiveness to second-line IVIG treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The best second line therapeutic methods for patients unresponsive to initial IVIG treatment is still uncertain. In an investigation of 5633 patients with Kawasaki disease in the United States, methylprednisolone was used as the second line therapy in 196 patients (27.1%) among the 722 patients unresponsive to initial IVIG [20] . IVIG was the second line drug of choice in 466 patients (64.5%) in this investigation.…”
Section: Unresponsive To Ivig Treatmentmentioning
confidence: 99%
“…In these patients with refractory KD, a second IVIG infusion is often administered, a cumulative dose of 4 g/kg. There is substantial practice variability in the treatment of refractory KD in the absence of clear consensus guidelines or definitive clinical trials . Recently Ebato and colleagues have proposed a strategy for the effective prevention of coronary artery aneurysm in refractory KD.…”
mentioning
confidence: 99%
“…There is substantial practice variability in the treatment of refractory KD in the absence of clear consensus guidelines or definitive clinical trials. 4 Recently Ebato and colleagues 5 have proposed a strategy for the effective prevention of coronary artery aneurysm in refractory KD. This study utilized an algorithmic approach that included infliximab or plasma exchange for patients resistant to IVIG and pulse steroids.…”
mentioning
confidence: 99%